Different loading schemes in power training during the preseason promote similar performance improvements in Brazilian elite soccer players - Loturco, I.; Urginowitsch, C.; Tricoli, V.; Pivetti, B.; Roschel, H. (The Journal of Strength and Conditioning Research, 2013)
The present study investigated the effects of 2 different power training loading schemes in Brazilian elite soccer players. Thirty-two players participated in the study. Maximum dynamic strength (1RM) was evaluated before (B), at midpoint (i.e., after 3 weeks; T1), and after 6 weeks (T2) of a preseason strength/power training. Muscle power, jumping, and sprinting performance were evaluated at B and T2. Players were randomly allocated to 1 of 2 training groups: velocity-based (VEL: n = 16; age, 19.18 ± 0.72 years; height, 173 ± 6 cm; body mass, 72.7 ± 5.8 kg) or intensity-based (INT: n = 16; age, 19.11 ± 0.7 years; height, 172 ± 4.5 cm; body mass, 71.8 ± 4.6 kg). After the individual determination of the optimal power load, both groups completed a 3-week traditional strength training period. Afterward, the VEL group performed 3 weeks of power-oriented training with increasing velocity and decreasing intensity (from 60 to 30% 1RM) throughout the training period, whereas the INT group increased the training intensity (from 30 to 60% 1RM) and thus decreased movement velocity throughout the power-oriented training period. Both groups used loads within ±15% (ranging from 30 to 60% 1RM) of the measured optimal power load (i.e., 45.2 ± 3.0% 1RM). Similar 1RM gains were observed in both groups at T1 (VEL: 9.2%; INT: 11.0%) and T2 (VEL: 19.8%; INT: 22.1%). The 2 groups also presented significant improvements (within-group comparisons) in all of the variables. However, no between-group differences were detected. Mean power in the back squat (VEL: 18.5%; INT: 20.4%) and mean propulsive power in the jump squat (VEL: 29.1%; INT: 31.0%) were similarly improved at T2. The 10-m sprint (VEL: -4.3%; INT: -1.6%), jump squat (VEL: 7.1%; INT: 4.5%), and countermovement jump (VEL: 6.7%; INT: 6.9%) were also improved in both groups at T2. Curiously, the 30-m sprint time (VEL: -0.8%; INT: -0.1%) did not significantly improve for both groups. In summary, our data suggest that male professional soccer players can achieve improvements in strength- and power-related abilities as a result of 6 weeks of power-oriented training during the preseason. Furthermore, similar performance improvements are observed when training intensity manipulation occurs around only a small range within the optimal power training load.